Chitosan and oligochitosan enhance ginger (Zingiber officinale Roscoe) resistance to rhizome rot caused by Fusarium oxysporum in storage. (20th October 2016) - Liu, Yiqing; Wisniewski, Michael; Kennedy, John F.; Jiang, Yusong; Tang, Jianmin; Liu, Jia
Highlights: Chitosan and oligochitosan inhibit ginger rhizome rot in storage. Chitosan and oligochitosan (5 g/L) increase defense enzyme activity in ginger. Chitosan and oligochitosan (5 g/L) induce gene expression of defense enzymes. Chitosan and oligochitosan (5 g/L) reduce weight loss of rhizomes in storage. Abstract: The ability of chitosan and oligochitosan to enhance ginger ( Zingiber officinale ) resistance to rhizome rot caused by Fusarium oxysporum in storage was investigated. Both chitosan and oligochitosan at 1 and 5 g/L significantly inhibited rhizome rot, with the best control at 5 g/L. Chitosan and oligochitosan applied at 5 g/L also reduced weight loss, measured as a decrease in fresh weight, but did not affect soluble solids content or titratable acidity of rhizomes. The two compounds applied at 5 g/L induced β-1, 3-glucanase and phenylalanine ammonia-lyase enzyme activity and the transcript levels of their coding genes, as well as the total phenolic compounds in rhizome tissues. Therefore, the ability of chitosan and oligochitosan to reduce rot in stored rhizomes may be associated with their ability to induce defense responses in ginger. These results have practical implications for the application of chitosan and oligochitosan to harvested ginger rhizomes to reduce postharvest losses.